Improving Speaking Ability of Students in English Introduction Material Through Snowball Throwing Games in Class VII B SMPN 3 Surabaya - Kustiningsih, Endah Sri (Indonesian Journal of Contemporary Education, 2019)
The ability of students in class VII at SMPN 3 Surabaya to speak English is still low from year to year with indicators when expressing English verbally often stopping in the middle of a conversation, the average duration of speaking is under 5 minutes, using very limited vocabulary, lacking courage start talking in English both to the teacher and to classmates. The snowball throwing learning model is a type of cooperative learning that is designed like a ball throwing game. This method aims to provoke creativity in making questions while testing the absorption of material delivered by the group leader. By using the snowball throwing model in Classroom Action Research (CAR) conducted on students of class VII B in semester 1 of SMPN 3 Surabaya, it is expected that this game can improve students' speaking skills in English. Test instruments in the form of performance tests, formative and interviews were previously judged content by expert academics. From processing the formative performance test results in 2 cycles, the talk duration of students increased by an average of 8 minutes, mastery of vocabulary more with the use of diction better and correct, from the results of interviews showed students were more motivated to talk and learning was felt fun. It was concluded that the snowball throwing method was able to improve the speaking ability of VII B students of SMPN 3 Surabaya in English.